On r-Jacobsthal and r-Jacobsthal-Lucas numbers - Bilgici, Göksal; Bród, Dorota (Annales Mathematicae Silesianae, 2023)
Recently, Bród introduced a new Jacobsthal-type sequence which is called r-Jacobsthal sequence in current study. After defining the appropriate r-Jacobsthal–Lucas sequence for the r-Jacobsthal sequence, we obtain some properties of these two sequences. For simpler results, we define two new sequences and examine their properties, too. Finally, we generalize some well-known identities.